IDENTIFICATION OF DIFFERENT VARIETIES OF PUNARNAVA MENTIONED IN THE AYURVEDIC LITERATURE - Kumar Sanger, *Rupesh; Singh, D.C.; Chaubey, Suresh; Singh, Ritu; Verma, Sarita (International Journal of Ayurveda and Pharma Research, 2016)
Punurnava is one of controversial drug in Ayurveda. Nighantus have created a lot of confusion in the identification of different varieties of Punarnava mentioned in the Ayurvedic texts. Majority of the Nighantu used Varshabhu as the synonym of Punarnava. But later studies have proved that the two plants are totally different. In majority of Nighantus two varieties of Punarnava are found i.e Sveta and Rakta. Most of the people think Boerhaavia diffusa to be the red variety and Trianthema portulacastrum to be the white variety. But this is not correct. There are three plants which lie under this two category i.e Boerhaavia diffusa, Boerhaavia verticillata and Trianthema portulacastrum. On the basis of colour White and Red variety are differentiated. But with the colour what is to be taken whether the colour of the stem or the colour of the flowers. Punarnava is one of the very important anti inflammatory medicinal herb. Nowadays it is used for Mutrala as well as for its Rasayana property. Therefore it is need for the identification of correct plant or the species to get the best therapeutic effect of the plant. This article is to find out the correct species, which one is to be taken as Sveta and which one to be taken as Rakta Punarnava.